High-Throughput Metabolomics Platform for the Rapid Data-Driven Development of Novel Additive Solutions for Blood Storage - Nemkov, Travis; Yoshida, Tatsuro; Nikulina, Maria; D’Alessandro, Angelo (Frontiers in Physiology, 2022)
Red blood cell transfusion is a life-saving intervention and storage a logistic necessity to make ~110 million units available for transfusion every year worldwide. However, storage in the blood bank is associated with a progressive metabolic decline, which correlates with the accumulation of morphological lesions, increased intra- and extra-vascular hemolysis upon transfusion and altered oxygen binding/off-loading kinetics. Prior to storage, red blood cells are suspended in nutrient formulations known as additive solutions to prolong cellular viability. Despite a thorough expanision of knowledge regarding red blood cell biology over the past few decades, only a single new additive solution has been approved by the Food and Drug Administration this century, owing in part to the limited capacity for development of novel formulations. As a proof of principle, we leveraged a novel high-throughput metabolomics technology as a platform for rapid data-driven development and screening of novel additive solutions for blood storage under both normoxic or hypoxic conditions. To this end, we obtained leukocyte-filtered RBCs and stored them under normoxic or hypoxic conditions in 96 well plates (containing polyvinylchloride plasticized with diethylhexylphthalate to concentrations comparable to full size storage units) in the presence of an additive solution supplemented with 6 different compounds. To inform this data-driven strategy, we relied on previously identified metabolic markers of the RBC storage lesion that associate with measures of hemolysis and post-transfusion recovery, which are the FDA gold standards to predict stored blood quality, as well as and metabolic predictors of oxygen binding/off-loading parameters. Direct quantitation of these predictors of RBC storage quality were used here – along with detailed pathway analysis of central energy and redox metabolism – as a decision-making tool to screen novel additive formulations in a multiplexed fashion. Candidate supplements are shown here that boost specific pathways. These metabolic effects are only in part dependent on the SO2 storage conditions. Through this platform, we anticipate testing thousands of novel additives and combinations thereof in the upcoming months.